Granulocyte maturation determines ability to release chromatin NETs and loss of DNA damage response; these properties are absent in immature AML granulocytes - Lukášová, Emilie; Kořistek, Zdeněk; Klabusay, Martin; Ondřej, Vladan; Grigoryev, Sergei; Bačíková, Alena; Řezáčová, Martina; Falk, Martin; Vávrová, Jiřina; Kohútová, Viera; Kozubek, Stanislav (Biochimica et biophysica acta, 2013)
Terminally-differentiated cells cease to proliferate and acquire specific sets of expressed genes and functions distinguishing them from less differentiated and cancer cells. Mature granulocytes show lobular structure of cell nuclei with highly condensed chromatin in which HP1 proteins are replaced by MNEI. These structural features of chromatin correspond to low level of gene expression and the loss of some important functions as DNA damage repair, shown in this work and, on the other hand, acquisition of a new specific function consisting in the release of chromatin extracellular traps in response to infection by pathogenic microbes. Granulocytic differentiation is incomplete in myeloid leukemia and is manifested by persistence of lower levels of HP1γ and HP1β isoforms. This immaturity is accompanied by acquisition of DDR capacity allowing to these incompletely differentiated multi-lobed neutrophils of AML patients to respond to induction of DSB by γ-irradiation. Immature granulocytes persist frequently in blood of treated AML patients in remission. These granulocytes contrary to mature ones do not release chromatin for NETs after activation with phorbol myristate-12 acetate-13 and do not exert the neutrophil function in immune defence. We suggest therefore the detection of HP1 expression in granulocytes of AML patients as a very sensitive indicator of their maturation and functionality after the treatment. Our results show that the changes in chromatin structure underlie a major transition in functioning of the genome in immature granulocytes. They show further that leukemia stem cells can differentiate ex vivo to mature granulocytes despite carrying the translocation BCR/ABL.
Keywords: kultivované buňky; messenger RNA; DNA Damage; Real-Time Polymerase Chain Reaction; Cell Differentiation; Tetradecanoylphorbol Acetate; poškození DNA; Chromobox Protein Homolog 5; chromozomální proteiny, nehistonové; Granulocytes; Neutrophils; Chromatin; Cell Proliferation; Leukemia, Myeloid, Acute; granulocyty; kvantitativní polymerázová řetězová reakce; western blotting; polymerázová řetězová reakce s reverzní transkripcí; Cells, Cultured; Blotting, Western; RNA, Messenger; Humans; fluorescenční protilátková technika; neutrofily; akutní myeloidní leukemie; Chromosomal Proteins, Non-Histone; proliferace buněk; tetradekanoylforbolacetát; Fluorescent Antibody Technique; Reverse Transcriptase Polymerase Chain Reaction; chromatin; hematopoetické kmenové buňky; buněčná diferenciace; homolog proteinu s chromoboxem 5; Hematopoietic Stem Cells; lidé